Diversity of tree vegetation in Mount Baung Natural Tourism Park utilization block, Pasuruan Regency - Ilyasa, Muhammad Hasan; Suheriyanto, Dwi (Biogenesis: Jurnal Ilmiah Biologi, 2024)
The high diversity of tree species found in natural forests contributes to their ability to maintain ecological balance. Mount Baung Natural Tourism Park is the conservation area in Pasuruan Regency, East Java that functions to protect biodiversity. The research aims to identify tree species, analyze tree diversity, and determine tree dominance with the importance value index (IVI). The research was conducted from February to March 2023 in Mount Baung Natural Tourism Park utilization block (MBNTP UB), Pasuruan Regency, East Java, Indonesia. The observation location was determined to be 37 points and plots were made in the point with a size of 20 m × 20 m for the tree phase, 10 m × 10 m for pole phase, 5 m × 5 m for the sapling phase, and 2 m × 2 m for the seedling phase. Data collected from field observations were analyzed to determine the Shannon diversity index using PAST 4.01. Tree dominance was analyzed using IVI. The research showed that 14 species from 8 tree families are found in MBNTP UB. The Fabaceae family is found to be abundant compared to other families. The highest number of individuals found in the seedling phase is Cassia glauca. Swietenia macrophylla has the highest individual’s number in the sapling, pole, and tree phases. The highest tree diversity is found in the tree phase. Diversity at the tree phase is classified as moderate, while at the seedling, pole, and sapling phase the diversity is low.